2004
DOI: 10.1002/pits.10190
|View full text |Cite
|
Sign up to set email alerts
|

Respecialization as a school psychologist: Education, training, and supervision for school practice

Abstract: Professional psychology is facing a looming crisis. On one hand, there is an oversupply of clinical psychologists-a group generally facing decreasing salaries and growing competition. On the other hand, there is a shortage of school psychologists-a group experiencing increasing salaries and expanded role opportunities. Unfortunately, though, educators and practitioners have not fully addressed the issue of respecialization. In a basic way, just as a physician who changes specialties pursues rigorous, 3-year re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Alleviating the shortage by respecialization is an alternative, but it too is couched in categorical terms (Crespi, 2001;Crespi & Politikos, 2004;Tharinger & Palomares, 2004). Perhaps the demands and rigidity of traditional training are encouraging alternatives.…”
Section: Personal Perspectivesmentioning
confidence: 96%
“…Alleviating the shortage by respecialization is an alternative, but it too is couched in categorical terms (Crespi, 2001;Crespi & Politikos, 2004;Tharinger & Palomares, 2004). Perhaps the demands and rigidity of traditional training are encouraging alternatives.…”
Section: Personal Perspectivesmentioning
confidence: 96%
“…Notably too, not all employment requires a doctorate. In describing areas of oversupply and shortages, Crespi and Politikos (2004) noted national shortages in school psychology, which require a 3-year graduate program culminating in a "specialist" postmaster's designation and State Department of Education credentialing as a school psychologist. (This is in contrast to a licensed psychologist with a doctorate and credentialing through a State Department of Health Services.)…”
Section: Inside the Job Marketmentioning
confidence: 99%
“…At the doctoral level, a postdoctoral respecialization program can offer an opportunity to change specialties in psychology. Crespi and Politikos (2004) provide a helpful look at respecialization. Just as a physician (MD/DO) changing from internal medicine to psychiatry might complete an additional residency, so psychologists with a doctorate, although not needing to acquire a second doctorate, might complete additional coursework and applied training(i.e., practicum and internship training).…”
Section: Is There Employment With Direct Services Not Requiring a License?mentioning
confidence: 99%
“…The choices can seem overwhelming. Crespi and Politikos (2004) noted that there are areas of both shortages and oversupply, with notable shortages in school psychology. Elsewhere the APA (2016) reported that only 3% of master's degrees are in forensic counseling, another growth field.…”
Section: Become a Recurring Contributormentioning
confidence: 99%